Rancang Bangun Kendali Kapal Jarak Jauh Berbasis LoRa - Aji Nugraha; Diana Alia; Eddi Eddi (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
The remote-control system on this Unmanned Surface Vessel (USV) or unmanned ship uses Long Range (LoRa) technology. LoRa was chosen because of its ability to transmit data over long distances with low power consumption, making it very suitable for applications in the maritime environment. The control system on the USV is responsible for controlling movement, so it involves several technologies and components that work together to ensure the USV can operate efficiently. The way a USV works involves several systems working together to allow the autonomous vehicle to operate on the water surface unmanned or without direct human intervention. Under Line of Sight (LOS) conditions, the range of LoRa-02 to control unmanned is success rate up to a distance of 100 meters and achieved a 100% for data transmission. However, in the Non-Line of Sight (NLOS) test, there was a decrease in the range of only 70 meters due to obstacles such as trees or other objects. The transmitted data comes from the wireless camera in the form of images with timestamp displayed in real-time. The display from the wireless camera is utilized for visual field monitoring and can be monitored remotely.